2005
DOI: 10.1103/physrevc.71.044311
|View full text |Cite
|
Sign up to set email alerts
|

γ-ray spectroscopy ofTe132through β decay of aSb132

Abstract: γ -ray spectroscopy of 132 Te, obtained from β − decay of a 132 Sb radioactive beam at the Holifield Radioactive Ion Beam Facility, was performed using the Clarion array. A significantly revised γ -decay scheme for 132 Te was obtained including a number of new, likely 2 + , states below 2.5 MeV and the removal of a 3 − state at 2280 keV. A simple shell-model interpretation is discussed for the low-lying levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 14 publications
1
31
0
Order By: Relevance
“…Based on shell model calculations, it has been found that all known states up to 10 + are given mostly by neutron excitations, while the newly found transitions depopulate states most likely arising from neutron and proton excitations. [18,19]. New transitions found in this work are given as gray/pink, thick arrows originating from states with tentative spin assignments.…”
Section: Spectroscopy Of Neutron-rich Nuclei Around 132 Snmentioning
confidence: 80%
See 2 more Smart Citations
“…Based on shell model calculations, it has been found that all known states up to 10 + are given mostly by neutron excitations, while the newly found transitions depopulate states most likely arising from neutron and proton excitations. [18,19]. New transitions found in this work are given as gray/pink, thick arrows originating from states with tentative spin assignments.…”
Section: Spectroscopy Of Neutron-rich Nuclei Around 132 Snmentioning
confidence: 80%
“…This gave the possibility to investigate nuclei close to the 132 Sn doubly-magic core, in which microsecond isomers were identified in previous works. This is the case of 132 Te, 133 Sb and 130 Sn [4,[18][19][20][21]. The analysis was based on double and triple γ-coincidence histograms constructed either requiring correlations among γ-rays prompt with fission events (an event with γ-ray fold larger than 4 recorded within 200 ns was considered a fission event) or requesting correlations between prompt and delayed transitions (a transition was considered delayed if it occured within 200 ns and 20 µs after the prompt event and was not associated with multiplicity higher than 3).…”
Section: Spectroscopy Of Neutron-rich Nuclei Around 132 Snmentioning
confidence: 98%
See 1 more Smart Citation
“…132 Te is one of the first radioactive neutron-rich nuclei in which the B(E2; 2 + 1 → 0 + 1 ) value was measured in projectile Coulomb excitation reactions of a RIB [1]. The excited states of 132 Te have been identified in a γ -γ measurement following the β − decay of 132 Sb [26]. The second excited state at 1665.3 keV discovered in the latter study decays predominantly to the 2 + 1 state by a 690.9 keV transition and to the ground state by a very weak 1665.3 keV transition [I γ (691 keV)/I γ (1665 keV) = 100(52)].…”
Section: This Leaves Still Open the Question: What Is The Appropriatementioning
confidence: 99%
“…From this observation, together with the coincidence conditions and the background subtraction procedure, it is clear that the 691-keV γ line represents the decay of a low-lying Coulomb-excited state of 132 Te. Indeed, a γ ray with this energy is known [26] in the decay scheme of 132 Te. It represents the (2 + 2 ) → 2 + 1 transition.…”
Section: This Leaves Still Open the Question: What Is The Appropriatementioning
confidence: 99%